Do Consumers Gamble to Convexify? - Thomas F. Crossley; Hamish Low; Sarah Smith (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
The combination of credit constraints and indivisible consumption goods may induce some risk-averse individuals to gamble to have a chance of crossing a purchasing threshold. One implication of this is that income effects for individuals who choose to gamble are likely to be larger than for the general population. Using UK data on gambling wins, other windfalls and durable goods purchases, we show that winners display higher income effects than non-winners but only amongst those likely to be credit-onstrained. This is consistent with credit-constrained, risk-averse agents gambling to convexify their budget set.
Keywords: D12; E21; D81; L83; 330; Gambling; Lotteries; Consumption; Durables; Konsum; Nachfrage; Liquiditätsbeschränkung; Dauerhafte Konsumgüter; Glücksspiel; Großbritannien